Historical Dynamics of Aceh in the Republic of Indonesia - Purba, Sampe L.; Yusgiantoro, Purnomo; Kuntjoro, Yanif Dwi; Sudibyo, Rachmat; Saragih, Herlina J.R. (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The Province of Nanggroe Aceh Darussalam, hereinafter referred to as the Province of Aceh since the pre-colonial era until now, has a specific and special relationship dynamics in the course of Indonesian history. In the pre-colonial period, Aceh had a strategic position and got the recognition of the major powers at that time. In the colonial war, there were two groups that played a very important role, namely the nobility (teuku) and the religious elite (teungku). These two groups go hand in hand in the war against the enemy, but there is also friction and competition between them. The Memorandum of Understanding between the Government of Indonesia and the Free Aceh Movement (Helsinki Agreement 2005) was a turning point for peace in Aceh. The important points agreed upon including the reintroduction of the Acehnese Qanun as a respect for the historical traditions and customs of the Acehnese people, and reflected in the contemporary law. Also, the Nanggroe Institution along with all the ceremonial attributes and rights will be established. Along with the conducive security in the Aceh region, it seems that the political attitude of the people in general is no longer too emotionally linked to the historical romance of past glory. The decreasing share of local parties in Aceh's DPRA can be seen as an indication of this. However, some views today see that there are still many things that have not been fulfilled according to the original intent of the Helsinki peace.